THE STRATEGIC LEADERSHIP IN ENTREPRENEURSHIP : A SYSTEMATIC LITERATURE REVIEW OF LEADERSHIP STYLES, INNOVATION, AND BUSINESS GROWTH - Noris Bagus Mulyo; Brillian Rosy; Novita Aprillia; Abdul Ghani Azmi; Fariza Rachman; Dian Palupi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2026)
Phenomenon/Issue: The dynamics of the global business environment, marked digital disruption, market uncertainty, and intensified competition, demand a strategic leadership role in entrepreneurship. This is due to the fact that business failures often occur as a result of weak leadership capacity in managing innovation and growth. Purpose: This study comprehensively analyzes the role of various strategic leadership styles in driving innovation and business growth within the context of entrepreneurship through a systematic literature review approach. Novelty: This study presents a holistic conceptual integration by linking the evolution of leadership styles (transformational, transactional, authentic, servant, and responsible leadership) to entrepreneurial performance based on the triple bottom line (economic, social, and environmental). Research Methods: This study use a Systematic Literature Review (SLR) approach based on PRISMA and bibliometric analysis from the Scopus database (2017–2026), covering 112 articles in total. Of these, 15 selected articles were analyzed using VOSviewer to map research trends, collaborations, and conceptual structures. Results: Research findings indicate that strategic leadership is a key catalyst for innovation, organizational adaptability, and business growth. Adaptive and visionary leadership styles have been proven to enhance organizational performance and strengthen competitive advantages in dynamic environments. Research Contributions: This study makes a theoretical contribution by strengthening the multidisciplinary literature and a practical contribution by formulating effective leadership strategies for entrepreneurs to achieve sustainable growth. The study is dominated by the fields of business, management, and accounting (36.6%), followed by social sciences (34.1%), economics (26.8%), and decision sciences (2.4%), reflecting the multidisciplinary of this research